Sistematik Review Pengaruh Story Telling terhadap Kemampuan Bahasa Ekspresif Anak Usia Prasekolah - Sudarman, Sudarman; Gunawan, Gunawan; Nugroho, Setyadi (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Child development is a form of continuous and natural stages, therefore each aspect that is developed influences each other. One aspect of development that greatly influences children is language development, both receptively (understanding) and expressively (expression). One of the factors that influences language development is early reading practice (early literacy) and storytelling. Early literacy skills are the knowledge, attitudes and skills of an early age child related to reading and writing before mastering formal skills at school age. The components of early literacy are reading interest, language skills, phonological awareness, reading skills, and writing skills. In addition to early age reading skills (literacy), to improve expressive language skills, also by getting children used to telling stories (story telling). Story telling is a mechanism for conveying stories using words, images, sounds, or movements with the intention of communicating messages or influencing the audience. Objectives: This study is to determine the effect of Early Literacy Skills and Story Telling on the Expressive Language Skills of Preschool Children. Methods: This study design uses a systematic review conducted by searching and selecting various kinds of data from the results of previous research and data from the results of clinical trials conducted across ethnicities, races, and also the location in the world, the time of the study results to be selected is in the period 2000-2023. The article search will be conducted for a maximum of 2 months. Instrument: Research data is searched from databases, including: PubMed and Google Scholar. Results: By using the search keywords